Pengaruh Lingkungan Kerja Fisik, Motivasi Intrinsik, Dan Work Life Balance Terhadap Produktivitas Kerja Karyawan Generasi Z Dalam Konteks Work From Cafe (Wfc) Kabupaten Ponorogo - Putri Perdani (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2026)
This study is based on the background of the increasing trend of work from cafe (WFC) among Generation Z in the flexible work era. The study aims to analyze the influence of the physical work environment, intrinsic motivation, and work-life balance on the work productivity of Generation Z employees. Data analysis was analyzed using SPSS version 27 through validity (validity) and consistency (reliability) testing, multiple linear regression, t testing, F testing, and determination coefficient values. The findings of the study show that the physical working environment and intrinsic motivation do not have a significant impact on work productivity, while work-life balance has a positive and meaningful impact. Together, these three variables have a significant influence on work productivity with a determination coefficient value of 96.5%. This research indicates that the balance between personal life and work activities is the main factor in increasing work productivity in a flexible work system.